Green Synthesis and Modification of RuO2 Materials for the Oxygen Evolution Reaction - Devadas, Abirami; Baranton, Stève; Coutanceau, Christophe (Frontiers in Energy Research, 2020)
A dynamic ion-exchange method is proposed as a green synthesis route to prepare hydrous ruthenium oxide nanoparticles (H-RuO2 NPs). Physicochemical characterizations indicate that RuO2 crystalline rutile nanoparticles (NPs) are obtained either by direct calcination of the H-RuO2 material at 350 °C (C-RuO2) or by treatment under microwave irradiation of an aqueous suspension of H-RuO2 NPs with 20 vol. % ammonium hydroxide and calcination of the treated H-RuO2 material at 350 °C (A-C-RuO2). The electrocatalytic performances of the H-RuO2, C-RuO2 and A-C-RuO2 catalysts towards the oxygen evolution reaction (OER) are evaluated and compared in a 0.50 mol L-1 H2SO4 electrolyte. The H-RuO2 material displays the low onset potential of ca. +1.40 V vs RHE but is not stable for potentials higher than +1.500 V vs RHE. Improved performances towards the OER, in terms of activity and stability, are obtained with the C-RuO2 catalyst, but the higher catalytic activity is achieved by the ammonia treated A-C-RuO2 catalyst. The characterization of materials by X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy shows that the microstructure is affected by the ammonium hydroxide treatment under microwave irradiation: the A-C-RuO2 material displays lower crystallinity level and hydrous rutile content, and smaller mean crystallite size than those determined for the C-RuO2 one. Structure-property correlation has been established to give insights on the higher electrocatalytic activity of the A-C-RuO2 catalyst than that of the C-RuO2 one.